2012
DOI: 10.1108/00012531211263120
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS information and changing sexual behaviour among undergraduate students in Tanzania

Abstract: Purpose -This paper aims to investigate the level of HIV/AIDS information among undergraduate students at two university colleges in Tanzania, and its role in changing risky sexual behaviour. Design/methodology/approach -In total, 151 undergraduate students from Kilimanjaro Christian Medical College and Moshi University College of Cooperative and Business Studies were surveyed by means of a questionnaire. Findings -Of respondents 86 per cent were aware of the pandemic and its modes of transmission. The main so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…A study of PLHIV in Iringa revealed that health-care providers, television, radio, relatives and religious leaders were the major sources of HIV information (Rumisha et al, 2006). Another study in Kilimanjaro showed that the major sources of HIV information and young people were print materials (such as books, journals, magazines and research reports) and other sources (television, internet, DVD/CD, radio) (Mosha and Manda, 2012). These studies demonstrate that internet technologies are yet to be fully used by PLHIV in Tanzania to get access to HIV information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of PLHIV in Iringa revealed that health-care providers, television, radio, relatives and religious leaders were the major sources of HIV information (Rumisha et al, 2006). Another study in Kilimanjaro showed that the major sources of HIV information and young people were print materials (such as books, journals, magazines and research reports) and other sources (television, internet, DVD/CD, radio) (Mosha and Manda, 2012). These studies demonstrate that internet technologies are yet to be fully used by PLHIV in Tanzania to get access to HIV information.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on HIV information seeking behaviour in Africa is scarce and tends to focus on preferences of information sources, and effects of demographic factors on information seeking behaviour (Bastien et al, 2009;Mosha and Manda, 2012;Rumisha et al, 2006). Little attention is given to online information seeking behaviour, outcomes associated with online information seeking behaviour and factors that enhance usage intentions and actual usage of internet to get access to HIV information.…”
Section: Introductionmentioning
confidence: 99%